Goswami, U. (1998). Cognition in Children. East Sussex, UK: Psychology Press. 328 págs - Sylvia Sastre i Riba (Universidad de La Rioja, 2013)
Goswami, U. (1998). Cognition in Children. East Sussex, UK: Psychology Press. 328 pags.